Traditional and Digital Communication Media Publication Trends: A Systematic Literature Review - Machmud, Muslimin; ., Salahudin; Rijal, Najamuddin Khairur; Anugrah, Muh. (Journal of Ecohumanism, 2024)
This study aims to review publication and research trends; map research topic clusters, and determine the relationship between topics, and research topic trends on traditional communication media and digital communication media. The Systematic Literature Review (SLR) approach was applied in writing this article which used 33 scientific articles sourced from the Scopus database selected for publication between 1985 and 2024. Article analysis/review used Vosviewer software to map research topic networks and trends. This study revealed that the trend of scientific publications on the topics studied showed an increasing trend in the number of publications but was not significant from year to year, 1985 to 2024. The topic was studied from various fields of science through different approaches carried out intensively by scholars from developed countries. There are three topic clusters in this study, namely interaction clusters, applications, and uses that are interrelated with each other related to the use of traditional communication media and digital communication media as channels for sustainable development communication. The contribution of this study is to provide an overview of the importance of using traditional communication media that is integrated with the use of digital media so that both media can develop simultaneously. The limitation of this study is that the source of the articles used is only from the Scopus database so that it does not completely describe the trend of scientific publications on the topic being studied. The recommendation for the next study is a study using article sources from various reputable international databases.